2001
DOI: 10.1177/08959374010150011101
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and Age-related Differences in Primary and Secondary Dentin Formation

Abstract: -Clinical studies carried out on dentin thickness in adults, as well as experimental studies carried out on ovariectomized animals, indicate that odontoblast activity, like that of osteoblastic cells, differs in the two sexes. To examine the evidence for differences in odontoblast activity before puberty, we have measured dentin thickness and other crown dimensions from bitewing radiographs of the lower first molars in 240 children aged 4-16 years. The radiographs were obtained from pedodontic clinics througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 16 publications
(16 reference statements)
1
56
0
Order By: Relevance
“…In a study of molars of karyotypically normal individuals, Stroud et al (1994Stroud et al ( , 1998 found similar patterns of differences between sexes: the amount of enamel did not differ significantly, while that of dentine did. The data presented here support some of these studies in recognizing that male molars are endowed with proportionally more dentine (e.g., Stroud et al, 1994;Zilberman and Smith, 2001), though similar amounts of both tissues are present in each sex when overall differences in tooth size are taken into account. Taken together, the results of these studies corroborate those based on individuals with various sex chromosome anomalies, and demonstrate considerable independence between the regulatory mechanisms of dentine and enamel development.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In a study of molars of karyotypically normal individuals, Stroud et al (1994Stroud et al ( , 1998 found similar patterns of differences between sexes: the amount of enamel did not differ significantly, while that of dentine did. The data presented here support some of these studies in recognizing that male molars are endowed with proportionally more dentine (e.g., Stroud et al, 1994;Zilberman and Smith, 2001), though similar amounts of both tissues are present in each sex when overall differences in tooth size are taken into account. Taken together, the results of these studies corroborate those based on individuals with various sex chromosome anomalies, and demonstrate considerable independence between the regulatory mechanisms of dentine and enamel development.…”
Section: Discussionsupporting
confidence: 77%
“…Perhaps this is not surprising, as sex differences in dentine thickness are already present in the earliest stages of odontogenesis and become even more marked after puberty (Zilberman and Smith, 2001). The acceleration of differences in dentine thickness during the postpubertal period suggests the presence of dimorphism in odontoblastic activity throughout life (Woods et al, 1990; Solheim, 1992;Zilberman and Smith, 2001). The potential link between odontoblast function and sex hormones (in particular, estrogen; e.g., Hietala et al, 1998) and the degree of sexual dimorphism between teeth that initiate early and late in the growth period will be a fruitful area of future research.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A number of investigations have established that sexual dimorphism exists in the permanent dentition of humans particularly in the canines, which exhibit the greatest degree of difference [2,11,12,14,15,[19][20][21]. According to Butler [22] and Garn et al [15], a ''canine field'' exists in the permanent dentition around which adjacent teeth (lateral incisors and first premolars) share a tendency for greater sexual dimorphism than do more distant teeth.…”
Section: Introductionmentioning
confidence: 97%
“…However, a number of other studies have used alternative measurements such as the mesiodistal and buccolingual cervical and diagonal diameters of teeth [7]. In addition, some investigations have examined the distances of molar cusps [8], while some more recent research has focused on studying crown tissue measurements since it has been proved that tooth formation and tissue proportions are highly regulated by sex-linked genes [9][10][11][12][13][14][15][16][17][18]. Sexual dimorphism in crown morphology and size of the permanent dentition is the result of the different amount of enamel, dentin, and pulp tissue between males and females.…”
Section: Introductionmentioning
confidence: 98%